Quality preservation and safety ensurement of a vegetable smoothie by high-pressure processing - Fernandez, María Verónica (2019)
This research aims to evaluate the effect of a previously optimized high‐pressure processing (HPP) treatment on the vegetable smoothie stability during 28 days at 5 °C and on the inactivation of a contamination with Listeria monocytogenes and Escherichia coli O157:H7 surrogates during 12 days at 15 °C. HPP (630 MPa/6 min) reduced native microbiota to values below detection limit (DL = 1 log CFU/g) and significantly reduced polyphenol oxidase, peroxidase, and pectin methylesterase initial activities (16.7%, 29.6%, and 70.7%, respectively), maintaining significant lower values than control during storage. In addition, smoothie's soluble solids and pH were neither modified with treatment nor storage time, while greater retention of color and nutritional indicators was noted on treated samples during storage. Moreover, HPP allowed controlling 6 log CFU/g surrogate counts, maintaining them below DL during storage. Hence, optimized HPP treatment is effective to improve the quality stability of the product besides ensuring their safety when contamination occurs.